Media Sosial Sebagai Wadah Eksistensi Mahasiswa - Marhaning, Dwi Putri; Saroya , Apriliani; Sijabat, Rauly (UNIVERSITAS SERAMBI MEKKAH, 2025)
This study is about how students experience and interpret the impact of social media on brand existence. In this study, research partners are active students from various universities who have significant activities on social media. Research partners are selected based on several criteria, namely students who actively use social media as a means to communicate, interact, or display their identity in various aspects of academic and social life. The social media in question includes popular platforms such as Instagram, Twitter, TikTok, and Facebook. The selection of research partners is carried out through a purposive sampling approach, where researchers choose students who are specifically seen to have an existence on social media, either through the content they create, interactions with followers, or their involvement in various online communities or discussions. By selecting research partners that meet these criteria, researchers can dig deeper into the role of social media in shaping their existence. The results of the study found that Student Behavior towards Self-Existence: Behavior on social media can create a sense of community and identity, which contributes to self-existence. For example, sharing academic achievements or personal experiences can increase students' sense of existence in the digital world. Time Management towards Self-Existence: With effective time management, students can allocate time to interact on social media without neglecting academic responsibilities, which supports their self-existence. Self-Image towards Self-Existence: A positive self-image, built through interactions on social media, can strengthen self-existence. Students who feel accepted and appreciated on social platforms tend to have a stronger sense of existence.